9m-20=-76+m

Simple and best practice solution for 9m-20=-76+m equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9m-20=-76+m equation:


Simplifying
9m + -20 = -76 + m

Reorder the terms:
-20 + 9m = -76 + m

Solving
-20 + 9m = -76 + m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-1m' to each side of the equation.
-20 + 9m + -1m = -76 + m + -1m

Combine like terms: 9m + -1m = 8m
-20 + 8m = -76 + m + -1m

Combine like terms: m + -1m = 0
-20 + 8m = -76 + 0
-20 + 8m = -76

Add '20' to each side of the equation.
-20 + 20 + 8m = -76 + 20

Combine like terms: -20 + 20 = 0
0 + 8m = -76 + 20
8m = -76 + 20

Combine like terms: -76 + 20 = -56
8m = -56

Divide each side by '8'.
m = -7

Simplifying
m = -7

See similar equations:

| 2x(x-1)=10-2x | | Y=18x+12x^2-0.2x^3 | | -5x-22=-22 | | 31p=-124 | | 33=4(x-4)+9 | | 11-4m=15 | | (k+2)x^2-2kx-k=0 | | a(A-2)+2=11-2a | | 13-x=6-x | | 7a*a-12a+18=0 | | 4p-3q-p+5q= | | 3*(cos*2*x)=0 | | 4x-11=2x-7 | | X/4=.96 | | 6x-5=8x-2 | | -0.3x+8.22=-0.8x+6.22 | | (4z-9)(4+z)=0 | | sin(7x)=0.68 | | 6x-23=-5+9x | | (2+i)x+(1-3i)y-4-16i=0 | | z^3+2z^2-16=0 | | 2c-d= | | 12x-3=10x-5 | | 4x-55-(2x-50)=0 | | 16-1/2*32 | | 2x-30/100=170 | | 1/4x-8=8 | | 16-1/2*2 | | 16-1/2y | | -15n^2+8n+1=0 | | -1/2(16-8x) | | 5(2-3x)=x-14 |

Equations solver categories